Gut Microbiome Alterations in Patients with Severe Traumatic Brain Injury: A Feasibility Study - Albert, Venencia; Subramanian, Arulselvi; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
Severe traumatic brain injury (sTBI) is associated with significant morbidity and mortality. Emerging evidence from animal studies suggests a potential role for the gut microbiome in modulating systemic inflammation and neurological outcomes following TBI. However, the association between gut microbiome composition and the clinical course and neurological outcome in sTBI patients has not been extensively studied. This study aims to test the feasibility of exploring the potential association between gut microbiome composition, clinical course, and neurological outcomes in patients with sTBI.A prospective longitudinal pilot study was conducted, recruiting patients with sTBI based on the Glasgow Coma Scale at the emergency department. Fecal samples for microbiota analysis using 16S rRNA gene sequencing with nanopore long-read technology were collected within the first 24 hours after injury and on the 7th day post-injury.Metagenomic analysis revealed significant alterations in gut microbiome composition following TBI. A marked decrease in beneficial commensals such as Prevotella copri and Lactobacillus was observed, while opportunistic and potentially pathogenic species like Klebsiella pneumoniae and Bacteroides fragilis increased. Alpha and β diversity analyses confirmed a significant shift in microbial diversity, with a distinct separation between pre- and post-injury samples.This pilot study provides preliminary evidence of gut microbiome alterations following sTBI and supports the feasibility of conducting a larger scale study. The findings highlight the potential of microbiome-targeted interventions in TBI management.
Keywords: traumatic brain injury; gut microbiome; neurological outcomes; pilot study; feasibility